Influence of previous crops and nematicide treatments on root lesion nematode populations and crop yields - Kimpinski, J.; Edwards, L.M.; Gallant, C.E.; Johnson, H.W.; MacLeod, J.A.; Sanderson, J.B. (Phytoprotection)

(untitled) (Société de protection des plantes du Québec (SPPQ)l, 1992)
A field study assessing the influence of the previous crop, the crop sequence, and aldicarb treatments on root lesion nematode populations and crop yields was carried out in Prince-Edward-Island, Canada. The most recent crop had the greatest impact on nematode numbers. The crop sequences had an influence in some cases on root lesion nematode populations (primarily Pratylenchus penetrans) and on crop yields. In commercial barley (Hordeum vulgare) fields, root lesion nematodes in roots were greatest when barley followed a red clover (Trifolium pratense) timothy (Phleum pratense) ley, and stunt nematodes (Tylenchorhynchus spp., primarily T. dubius, and Merlinius spp.) were more common when barley followed barley. The combined dry weight of foliage and grain was larger when barley was planted after potato (Solanumtuberosum) and smaller when barley followed barley or a red clover-timothy mixture. Under experimental field conditions, root lesion nematode populations were largest in barley roots when barley followed potato and grain yields were smallest when barley followed barley. Changes in nematode populations in potato were not associated with crop sequences. Potato tuber yields were higher in the sequences that began with wheat (Triticum aestivum) or barley than in the sequences that began with potato or soybean (Glycine max). Aldicarb reduced the numbers of root lesion nematodes in roots with concomitant yield increases in potato and soybean.